1988
DOI: 10.1152/jappl.1988.65.1.264
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of airway mucosal perfusion and water volume with an inert soluble gas

Abstract: The purpose of this study was to develop and validate a new in vivo technique for the measurement of tracheal mucosal blood flow (Qtr) and tissue water volume (VH2O) with an inert soluble gas. The technique was based on the notion that the uptake of dimethyl ether (VDME) from an isolated tracheal segment is governed by VH2O (transient state) and Qtr (steady state). In lightly anesthetized sheep, an endotracheal tube with two cuffs placed 14.5-16.5 cm apart was placed to create a chamber into which dimethyl eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These findings are in agreement with those of Barker and colleagues (2), who demonstrated that local exposure of the tracheal mucosa to inhaled isoproterenol resulted in a dose-dependent increase in tracheal mucosal blood flow. However, Wanner et al (27) measured only the tracheal mucosal blood flow by the inert soluble gas technique using dimethyl ether, whereas we measured the total bronchial arterial blood flow directly with an ultrasonic flow probe, a technique that measures the total blood flow to the airway mucosa as well as that supplying the entire airway wall. Q br progressively increased with higher doses of isoetharine HCl and ultimately reached a plateau.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with those of Barker and colleagues (2), who demonstrated that local exposure of the tracheal mucosa to inhaled isoproterenol resulted in a dose-dependent increase in tracheal mucosal blood flow. However, Wanner et al (27) measured only the tracheal mucosal blood flow by the inert soluble gas technique using dimethyl ether, whereas we measured the total bronchial arterial blood flow directly with an ultrasonic flow probe, a technique that measures the total blood flow to the airway mucosa as well as that supplying the entire airway wall. Q br progressively increased with higher doses of isoetharine HCl and ultimately reached a plateau.…”
Section: Discussionmentioning
confidence: 99%
“…The same principle was applied to measure the blood flow of the airways15 making use of dimethylether (DME), a soluble gas with a high affinity for haemoglobin. This method is based on the assumption that the uptake of an inert soluble gas in a tissue with capillaries and active flow of blood is determined by the volume of the tissue and by the blood flow 16.…”
Section: Measurement Of Bronchial Blood Flowmentioning
confidence: 99%
“…The effect of aerosolized phenylephrine on tracheal mucosal blood flow has been studied by Barker et al (1) in a sheep model. In their study, tracheal mucosal flow was measured by an inert soluble gas technique using dimethyl ether (15). Barker and colleagues found that phenylephrine administered as an aerosol reduced mucosal blood flow in a dose-dependent manner and that this response was partially blocked by phentolamine (1).…”
Section: Discussionmentioning
confidence: 99%